Analysis of Outpatient Patient Satisfaction in Jagakarsa District Health Center, South Jakarta - Fathiyati, Fathiyati (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
Health Center is a technical unit the District Health Office/City held responsible health development in a work area. By national standards work area is a sub-district health centers. Development vision health clinic is organized by the achievement of a healthy district towards the realization of Healthy Indonesia in 2010. To achieve this vision, the organizing efforts of individual health centers and community health efforts. The research problem is still there as much as ± 45 % of patients who complain of dissatisfaction with the district health center services gadung Pulo in East Jakarta . While the purpose of the study was to describe patient satisfaction in an outpatient General Poly Health Center gadung Pulo in East Jakarta District in 2013. Chi-square test results showed that the variables associated with patient satisfaction are age with p value = 0.008, p variable work with value = 0.049 and socioeconomic status variables with p value = 0.010. Results of logistic regression showed that the most dominant factors linked to patient satisfaction are age variable after control with variable socioeconomic status. Her recommendation in this research is to establish the system implementation strategy is appropriate and effective services so as to stimulate employees to improve performance and further services can positively impact the patient satisfaction. Contribute to the development of science in an effort to improve the relevance and equivalence between academic substance with the knowledge and skills especially in the field of administration of health centers/hospitals are in this case related to the development of management science in health centers/hospitals and broaden knowledge in order to develop knowledge public health, especially on the management and development services in health centers